2021
DOI: 10.5114/jcb.2021.106241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy and safety of iodine-125 seeds implantation in the treatment of patients with inoperable early-stage non-small cell lung cancer

Abstract: Purpose: To evaluate the efficacy and safety of iodine-125 ( 125 I) seeds implantation for inoperable early-stage nonsmall cell lung cancer (NSCLC).Material and methods: PubMed, Cochrane Library, Embase, China Biology Medicine disc (CBM), China National Knowledge Infrastructure (CNKI), and Wanfang Data were searched from inception until April 2020. Data were collected concerning overall survival, short-term efficacy, and complications. Meta-analysis was performed using R software (version 3.6.3).Results: Nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Implanted iodine-125 seeds can continuously release low-dose γ-rays and X-rays, with a radiation radius of 1.7 cm and a half-life of 59.6 days. Iodine-125 seeds release a cumulative radiation dose of 110-160 Gy in 8-10 months, with only a negligible radiation dose to surrounding tissues [ 11 ]; therefore, brachytherapy is a highly precise local therapy, and is superior to SBRT in terms of extremely low-risk of radiation-related adverse reaction [ 23 ]. This advantage is more obvious in peripherally and centrally located tumors, just as in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Implanted iodine-125 seeds can continuously release low-dose γ-rays and X-rays, with a radiation radius of 1.7 cm and a half-life of 59.6 days. Iodine-125 seeds release a cumulative radiation dose of 110-160 Gy in 8-10 months, with only a negligible radiation dose to surrounding tissues [ 11 ]; therefore, brachytherapy is a highly precise local therapy, and is superior to SBRT in terms of extremely low-risk of radiation-related adverse reaction [ 23 ]. This advantage is more obvious in peripherally and centrally located tumors, just as in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…5 Computational and Mathematical Methods in Medicine of CT imaging big data-assisted arterial chemoembolization combined with 125 I seed implantation for NSCLC was higher than arterial chemoembolization alone, without significantly increasing the incidence of adverse reactions, suggesting that the combination treatment can effectively inhibit NSCLC progression. The reason for the results may be that 125 I radioactive seeds are a kind of long half-life particles and can emit continuously low energy gamma rays, which can enhance the self-sensitization of the tumor cells and improve the sensitivity and killability of cancer cells, thus greatly improving treatment effect [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Chen E. et al and Li et al studied brachytherapy without concomitant therapies and reported an efficiency of 90% and a local control (LC) rate of 99% when treating NSCLC. [ 26 , 27 ]. An increase in LC was related to a prescription dose higher than 120 Gy.…”
Section: Endobronchial Administrationmentioning
confidence: 99%
“…The addition of brachytherapy to the other modalities showed an increased effect, OS, PFS and QOL. The most common AEs related to internal radiotherapy are pneumothorax (19%), bleeding (14%) and radiation pneumonitis (6%) [ 26 , 27 ].…”
Section: Endobronchial Administrationmentioning
confidence: 99%
See 1 more Smart Citation